Sustainable development issues in scientific publications - Hanna Sikacz (Economic and Environmental Studies (E&ES), 2017)
The objective of the article is to present the results of bibliometric analysis of the scientific studies concerning the issue of sustainable development (SD). The analysis allowed identifying the main territories in the context of the above issues. For the purposes of the analysis was used bibliometric examination of the data available in the Web of Science database, the investigation of trends, in terms of number of publications, the method of cooccurrence of words, cluster exploration and also mind mapping method. In the analysis was used software VOSviewer. The analysis lets us extending the area of research relating to the issue of sustainable development to the following four sub-areas: (1) education for sustainable development, (2) resource efficiency, (3) technological solutions geared towards sustainable development and (4) regional scale sustainable development.
Keywords: Q01; Q25; Q55; Q56; R11; 330; sustainable development; education; resource; technology; region